2002
DOI: 10.1037/0097-7403.28.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of retroactive interference in human infants.

Abstract: In 3 experiments with 85 human 3-month-olds, the authors asked whether retroactive interference with their memory of the original training stimulus is temporary or permanent. Infants learned to move a mobile by kicking and then were exposed to a different mobile (Experiment 1) or context (Experiment 2) immediately or 3 days afterward (Experiment 3). They were tested after increasing delays with the original stimulus, the exposed stimulus, or a completely novel stimulus. Retroactive interference was temporary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…A closer look at the infant data, however, revealed that passive exposure to novel information permanently modified the original training memory only when it was older (Boller et al, 1996;Muzzio & Rovee-Collier, 1996;Rovee-Collier et al, 1994). What had initially seemed to be a memory modification resulting from passive exposure to novel information shortly after training (Rovee-Collier et al, 1993) turned out to be a relatively transient retroactive interference phenomenon (Gulya et al, 2002;Rossi-George & Rovee-Collier, 1999). Likewise, in the present study, passive exposure to novel information permanently modified the reactivated memory only when it was older.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…A closer look at the infant data, however, revealed that passive exposure to novel information permanently modified the original training memory only when it was older (Boller et al, 1996;Muzzio & Rovee-Collier, 1996;Rovee-Collier et al, 1994). What had initially seemed to be a memory modification resulting from passive exposure to novel information shortly after training (Rovee-Collier et al, 1993) turned out to be a relatively transient retroactive interference phenomenon (Gulya et al, 2002;Rossi-George & Rovee-Collier, 1999). Likewise, in the present study, passive exposure to novel information permanently modified the reactivated memory only when it was older.…”
Section: Discussioncontrasting
confidence: 55%
“…As a result, the reactivated memory is resistant to modification shortly after reminding (Galluccio, 2005), just as the original memory is resistant to modification shortly after training (Gulya et al, 2002;Rovee-Collier et al, 1994). Also like the original memory, the reactivated memory is more malleable when it is older (i.e., when more time has elapsed since its initial reactivation).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…If the retrieval deficit is transient, then the original memory is rendered temporarily inaccessible; however, after a longer delay the interference dissipates, and the original memory can again be retrieved. Gulya et al (2002) found that passively exposing 3-month-olds to a novel mobile immediately after training (without a distinctive context) led both to interference with and modification of their training memory 1 day later. When infants were tested 2 days later, the interference had dissipated, but they still recognized the novel exposure mobile.…”
Section: Experiments 3a: Persistence Of Interference After a Delayed Pmentioning
confidence: 98%
“…When the exposure occurred shortly after training, it retroactively interfered with infants' subsequent recognition of the original training mobile and context; that interference eventually dissipated, and recognition of the original mobile was recovered (Gulya, Rossi-George, & Rovee-Collier, 2002). But when the exposure occurred after a longer delay, the details of the novel mobile or context were substituted for those of the original training mobile or context, resulting in a permanent memory modification (Boller, Rovee-Collier, Gulya, & Prete, 1996;Rovee-Collier, Adler, & Borza, 1994).…”
mentioning
confidence: 96%